O chá e os settings : a experiência de estar em psicoterapia e fazer uso ritual da ayahuasca = The brew and the settings: the experience of being in psychoterapy and participating in ayahuasca rituals - Simão, Ana Carolina, 1990- (2018)
Orientador: Luís Fernando Farah de Tófoli